Worldwide Diffusion of Corporate Governance (CG) Regulations and Practices: A Literature Review - Zubair Ahmad; Zeeshan Mahmood (Journal of Accounting and Finance in Emerging Economies, 2015)
Research objectives: The main objective of this paper was to understand the diffusion of CG codes around the world. More specifically this paper examined what types of CG codes have emerged around the world? What causes the diffusion of shareholder centric model of CG around the world? What areas are still unexplained to better understand the diffusion of CG?